EVALUATION OF THE APPLICATION OF ACCOUNTING IN TRADITIONAL HANDICRAFT MICRO ENTERPRISES: A CASE STUDY AT UD. MANURUNG SILITONGA - Simorangkir, Helmina Handayani; Siahaan, Audrey M; Sinurat, Mangasa (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study aims to analyze the application of accounting in traditional handicraft MSMEs, especially the Ulos and Songket Tarutung Businesses at UD. Manurung Silitonga, Siatas Barita District, North Tapanuli Regency. The urgency of this research is driven by the low awareness of MSME actors in implementing an accounting system in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), thus having an impact on financial management and business growth. The method used is qualitative descriptive with data collection through observation, in-depth interviews, and documentation. The results show that financial recording is still carried out simply and not fully in accordance with accounting standards, due to low accounting understanding and limited human resources. The contribution of this research is to provide an understanding of the importance of the application of accounting for MSMEs in supporting decision-making and business sustainability. The novelty of the research lies in its focus on the traditional handicraft sector in the North Tapanuli region that has not been studied much before.